Changes in The Percentage of Spermato Genic Cells in White Mice Associated With Cadmium Administration - AI-Bairuty, J.A; Kadhim, A.H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The effect of different doses (75,100,150 ppm) and periods of treatment (3,6,9 days) on the spermatognic cells in white mice was studied. It was found that there was a significant decrease (P<0.05) in the percentage of spermatogonia specially in concentration 1 00 and 150 ppm lasted six and nine days and of primary spermatocytes at period of nine days. A significant decrease (P<0.05) was noticed in the percentages of secondary spermatoytes and spermatids, while the percentage of sperms illustrated a significant increase for all concentrations and treatment periods.